EP187/#614 Extracellular matrix levels modulate outgrowths dynamics in ovarian cancer. (4th December 2022) - Alshehri, Sarah; Pavlovic, Tonja; Farsinejad, Sadaf; Behboodi, Panteha; Quan, Li; Centeno, Daniel; Kung, Douglas; Rezler, Marta; Lee, Woo; Jasiński, Piotr; Dziabaszewska, Elżbieta; Nowak-Markwitz, Ewa; et al.
Abstract : Objectives: Ovarian carcinoma (OC) form outgrowths that extend from the outer surface of an afflicted organ into the peritoneum. OC outgrowth formation is poorly understood because there is a limited availability of OC cell culture models to examine the behavior of cell assemblies that form outgrowths. Methods: Prompted by immuno-chemical evaluation of extracellular matrix (ECM) components, laminin γ1 and collagens, in human tissues representing untreated and chemotherapy-recovered OC, we developed laminin and collagen-rich ECM-reconstituted cell culture models amenable to studies of cell assemblies that can form outgrowths. Results: We demonstrate that ECM promotes outgrowth formation in fallopian tube non-ciliated epithelial cells (FNE) expressing mutant p53 R175H and various OC cell lines. Outgrowths were initiated by cell assemblies that had undergone outward translocation and, upon mechanical detachment, could intercalate into mesothelial cell monolayers. Electron microcopy, optical coherence tomography (OCT) and small- amplitude oscillatory shear experiments revealed that elevating ECM levels increased ECM fibrous network thickness and led to high shear elasticity of ECM environment. These physical characteristics were associated with suppression of outgrowths. Culture environment with low ECM content mimicked viscoelasticity and fibrous networks of ascites and supported cell proliferation, cell translocation and outgrowth formation. Conclusions: These results highlight the importance of ECM microenvironments in modulating OC growth and could provide additional explanation of why primary and recurrent ovarian tumors form outgrowths that protrude into the peritoneal cavity containing ascites as opposed to breaking through the basement membrane and invading collagen-dense tissues.